Enhancement of ethanol electrooxidation in half cell and single direct ethanol fuel cell (DEFC) using post-treated polyol synthesized Pt-Ru nano electrocatalysts supported on HNO3-functionalized acetylene black carbon - Choudhary A.K.; Pramanik H. (My University, 2025)
Highly dispersed Pt-Ru nano electrocatalysts supported on functionalized acetylene black carbon (CAB) were synthesized by a modified polyol reduction route followed by post treatment under three different conditions. The synthesized Pt-Ru/CAB-syn electrocatalysts after post treatment were designated as Pt-Ru/CAB-H2-RT when treated under H2 atmosphere at room temperature of 40 °C, and Pt-Ru/CAB-H2-160 when treated under H2 atmosphere at 160 °C and Pt-Ru/CAB-Air-160 when treated under air at 160 °C, respectively. The post treatment of synthesized electrocatalyst modified the crystallographic and morphological structures of the synthesized electrocatalysts which enhanced the electrocatalytic activity for ethanol electrooxidation. The physical characteristics of the post-treated electrocatalysts were recorded using XRD, SEM-EDX and TEM techniques. The XRD and TEM analyses revealed that the synthesized electrocatalysts have particle size in nano range with narrow size distribution. The electrochemical study of synthesized electrocatalysts were evaluated via cyclic voltammetry and chronoamperometry revealed that the Pt-Ru/CAB-H2-RT electrocatalyst is the most active exhibit towards ethanol electrooxidation in comparison to that of Pt-Ru/CAB-H2-160, Pt-Ru/CAB-Air-160 and commercial Pt-Ru/C electrocatalysts. In DEFC performance test at a temperature of 40 °C, the obtained power density (9.15 mW/cm2) using the synthesized Pt-Ru/CAB-H2-RT as anode electrocatalyst was higher than that of Pt-Ru/CAB-Air-160 (5.79 mW/cm2), Pt-Ru/CAB-H2-160 (6.84 mW/cm2) and commercial Pt-Ru/C (7.86 mW/cm2) electrocatalysts with same anode electrocatalyst loading of 1 mg/cm2 and 2 M ethanol fuel. The maximum OCV of 0.737 V and power density of 16.23 mW/cm2 at 0.317 V with a current density of 51.2 mA/cm2 were obtained using Pt-Ru/CAB-H2-RT electrocatalyst as anode at a cell temperature of 80 °C. The enhanced and superior performance of Pt-Ru/CAB-H2-RT electrocatalyst after post treatment could be attributed to well alloyed microstructure and highly dispersed surface morphology of metal nanoparticles. © 2019 Hydrogen Energy Publications LLC